Peran Mahkamah Konstitusi terhadap Pemenuhan Hak Warga Negara atas Perumahan yang Layak (The Role of the Constitutional Court on the Fulfilment of Citizens’ Right to Adequate Housing) - Novianto Murti Hantoro (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2019)
The right to adequate housing is a part of economic, social and cultural rights. The judicial review of the law in housing sector shows that there are problems with this right and at the same time shows that the Constitutional Court has a role in handling its fulfilment issues. This paper aims to discuss the role of the Constitutional Court through legal considerations in its decision on review of the law in housing sector as well as its suitability with international legal instruments. The legal considerations of the Constitutional Court have paid attention to the interests of the government, private sector, and the citizen, and have been concerned with one aspect of the right to housing, namely affordability. Affordability should not neglect the aspect of adequate housing. The issue of adequate housing as a human right should come first before the issue of housing as a commodity. The obligation to fulfil this right rests with the state and is carried out by the government. There is also a disharmony between the Law on Housing and the Law on Regional Government. According to the Law on Regional Government, the Central Government has the responsibility to provide housing for low-income households. When in fact it should be a shared-responsibility of the central and regional governments. AbstrakHak atas rumah layak merupakan bagian dari hak ekonomi, sosial, dan budaya. Uji materi undang-undang di bidang perumahan menunjukkan adanya permasalahan atas hak tersebut dan MK memiliki peran dalam penanganan persoalan pemenuhannya. Tulisan ini bertujuan untuk membahas peran MK melalui pertimbangan hukum dalam putusannya terhadap uji materi undang-undang di bidang perumahan dan kesesuaiannya dengan instrumen hukum internasional. Pertimbangan hukum MK telah memerhatikan kepentingan pemerintah, pengusaha, dan masyarakat, serta telah sesuai dengan salah satu aspek dalam hak atas perumahan, yaitu keterjangkauan biaya. Keterjangkauan biaya tidak seharusnya mengabaikan aspek kelayakan. Persoalan perumahan sebagai hak asasi perlu lebih diutamakan dibandingkan perumahan sebagai komoditas. Kewajiban untuk memenuhi hak tersebut berada di tangan negara dan dilaksanakan oleh pemerintah. Terdapat disharmoni antara UU Perumahan dan UU Pemda. Dalam pembagian urusan, penyediaan rumah untuk MBR di UU Pemda hanya menjadi kewenangan Pemerintah Pusat. Urusan penyediaan rumah untuk MBR seharusnya menjadi tanggung jawab Pemerintah Pusat dan pemerintah daerah.